Factors affecting decision-making in Gaelic Football: a focus group approach - McLoughlin, Emma Jane M.; Broadbent, David P.; Kinrade, Noel P.; Coughlan, Edward K.; Bishop, Daniel T. (Frontiers in Psychology, 2023)
Objectives: Research examining decision-making in sport has predominantly used experimental approaches that fail to provide a holistic understanding of the various factors that impact the decision-making process. The aim of the current study was to explore the decision- making processes of Senior (expert) and Academy (near-expert) Gaelic Football players using a focus group approach. Methods: Four focus groups were conducted; two with Senior players (n=5; n=6) and two with U17 Academy players (n=5; n=6). In each focus group, short video clips of Senior Gaelic football games were played, and the action was paused at key moments. The group then discussed the options available to the player in possession, the decision they would make in that situation, and importantly, what factors influenced the final decision. Thematic analysis was used to identify themes that emerged from the focus groups. Results and Discussion: Four primary themes emerged that affected the decision-making process. Three themes were related to information sources, namely, pre-match context (coach tactics and instructions, match importance and opposition status), current match context (score, time remaining), and visual information (player positioning and field space, visual search strategy), and the fourth theme related to individual differences (self-efficacy, risk propensity, perceived pressure, physical characteristics, action capabilities, fatigue) that moderated the decision-making process. Compared to the near-expert Academy players, the expert Senior players displayed a more sophisticated understanding of the various sources of information and were able to integrate them in a more complex manner to make projections regarding future scenarios. For both groups, the decision-making process was moderated by individual differences. A schematic has been developed based on the study findings in an attempt to illustrate the hypothesized decision-making process.